The Immigration Regulation and Control Problem of the European Union - KARACAN, Osman; KARACA, Yunus Emre (Bingol Universitesi, 2022)
After World War Two, Western Europe states started to receive migrants to fill labour shortages. With the end of the Cold War, the flow of immigrants to Europe accelerated, and the issue of immigration became one of the most important topics on the European Union’s agenda by the 2000s. In this context, this study seeks to answer whether European states have lost their immigration control. This study aims to clarify the internal and external reasons that adversely affect the capacity of European states to control immigration, focusing primarily on the developments since 1945. The immigration policies of the European Union (EU) are also discussed in this context. This study employed the qualitative research methodology. In the study, academic books and articles were used besides online newspapers and the official documents prepared by the EU. The study's findings demonstrate that although European states have not entirely lost their control over immigration, their current immigration policies are insufficient to stop the flow of immigration to Europe.
Keywords: European Union; EU; Immigration; Immigration Policy; Crisis; Border Control; Kamu Yönetimi; Public Administration; Avrupa Birliği; AB; Göç; Göç Politikası; Kriz; Sınır Kontrolü; 8. Economic growth; 16. Peace & justice; 10. No inequality